2009
DOI: 10.1111/j.1471-4159.2009.05909.x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of protein kinase Cα isozyme in the regulation of oxidative stress and neuropeptide Y gene expression in phenylpropanolamine‐mediated appetite suppression

Abstract: Hypothalamic neuropeptide Y (NPY) is an appetite stimulant in the brain. Although regulation of NPY expression has been reported to contribute to the appetite‐suppressing effect of phenylpropanolamine (PPA), it is still unknown if protein kinase C (PKC) is involved in this effect. Rats were daily treated with PPA for 4 days. Changes in food intake, hypothalamic NPY, PKC, and proopiomelanocortin (POMC) mRNA levels were assessed and compared. Results showed that the NPY gene was down‐regulated following PPA trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Numerous findings have revealed that PKC alpha is a mediator in the activation of stress-response kinase. Kuo DY et al demonstrated that PKC alpha knock-down could reverse the increase of SOD gene expression induced by phenylpropanolamine [22]. They revealed that PKC alpha signaling was an upstream mediator that regulates SOD gene expression, and the increase in SOD induced by PKC alpha can reduce oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous findings have revealed that PKC alpha is a mediator in the activation of stress-response kinase. Kuo DY et al demonstrated that PKC alpha knock-down could reverse the increase of SOD gene expression induced by phenylpropanolamine [22]. They revealed that PKC alpha signaling was an upstream mediator that regulates SOD gene expression, and the increase in SOD induced by PKC alpha can reduce oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that the cPKCα isotype, which depends on Ca 2+ and DAG during activation (Kuo et al. 2009b), was involved in the regulation of NPY‐mediated PPA anorexia.…”
Section: Discussionmentioning
confidence: 99%